FUZZY NEURAL NETWORKS IN INTELLIGENT MANUFACTURING SYSTEMS - Setlak, Galina (International Journal of Computing, 2002)
This paper presents fuzzy neural networks, which are an expansion of classical neural networks. These networks can formally represent and process both the qualitative (linguistic) and quantitative information, which usually describe a complex, multidimensional systems or decision making processes. The second part presents the results of tests and a practical implementation of applications for decision support systems based on fuzzy neural networks used for strategic management and determination of product development strategy.